2021
DOI: 10.1002/casp.2534
|View full text |Cite
|
Sign up to set email alerts
|

Gods, germs, and science: Unraveling the role of scientific literacy, germ aversion, and religious fundamentalism in predicting attitudes towards gays and lesbians

Abstract: Prior studies suggest that scientific knowledge may improve attitudes towards sexual minorities such as gays and lesbians. But in what context does this ring true? The present study aims to test whether scientific literacy can predict attitudes towards gays and lesbians when considering the variables pathogen avoidance and religious fundamentalism in a moderated moderation model. A total of 1,398 participants (female = 74.9%, Mage = 25.15, SD = 5.84) completed our online survey. We found that an increase in sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…The Perceived Vulnerability to Diseases (PVD) scale (Duncan et al, 2009) was used to measure latent variables related to the BIS. We used a version of the scale that was translated to Bahasa Indonesia (Hudiyana et al, under review), and confirmed the two factors of the original scale, germ aversion (GA, McDonald’s ω = 0.69, Cronbach’s α = 0.69) and perceived infectability (PI, McDonald’s ω = 0.85, Cronbach’s α = 0.85), using confirmatory factor analysis (Rosseel, 2012). The scale uses a 4-point Likert scale (1 = Completely disagree, 4 = Completely agree).…”
Section: Methodsmentioning
confidence: 99%
“…The Perceived Vulnerability to Diseases (PVD) scale (Duncan et al, 2009) was used to measure latent variables related to the BIS. We used a version of the scale that was translated to Bahasa Indonesia (Hudiyana et al, under review), and confirmed the two factors of the original scale, germ aversion (GA, McDonald’s ω = 0.69, Cronbach’s α = 0.69) and perceived infectability (PI, McDonald’s ω = 0.85, Cronbach’s α = 0.85), using confirmatory factor analysis (Rosseel, 2012). The scale uses a 4-point Likert scale (1 = Completely disagree, 4 = Completely agree).…”
Section: Methodsmentioning
confidence: 99%